Content Analysis Method: Analisis Prinsip Isi dan Prinsip Kualitas Laporan Keberlanjutan - Chyntia Susanto; Helen Leonora; Carmel Meiden (Ekonomis: Journal of Economics and Business, 2022)
The sustainability report is one of the company's accountability and transparency tools, in relation to the achievement of the Sustainable Development Goals. Sustainability reports are important to stakeholders in relation to the company's Social and Environmental Responsibility. The increase in sustainability reporting as a result of the company's obligation to comply with the rules of the Government of Indonesia needs to be reviewed for compliance with the applicable and widely used reporting standards. GRI Standards as a widely used standard have extensive and interrelated preparation guidelines, with its reporting principles, namely the content principle and the quality principle as the basis for the preparation that must be applied. This study aims to determine and compare the compliance of sustainability reporting with the reporting principles of the GRI Standards. The object of the research is the companies listed in the SRI-KEHATI index on the Indonesia Stock Exchange in 2018-2021. The data collection technique in this research is the observation technique and the sample selection technique is the purposive sampling technique. The content analysis method is used as the research analysis technique. The results of this study indicate that in accordance with the indicators of reporting principles, the highest score obtained for the quantitative approach of content principle is the sustainability context principle, the highest score for the qualitative approach of content principle is the completeness principle, and the highest score for the qualitative and quantitative approaches of quality principle is the balance principle.